Patient adherence, satisfaction and changes in anthropometric parameters with e-health versus in-person monitoring in metabolic bariatric surgery patients: A study protocol for a systematic review and non-inferiority meta-analysis of cohort studies. - Maíra Ribas Goulart; Karine Elisa Schwarzer Schmidt; Gustavo Waclawovsky; Izabele Vian (PLoS ONE)
Background Obesity is a risk factor for cardiovascular diseases and associated with reduced life expectancy metabolic bariatric surgery (MBS) is the treatment indicated when patients are unable to lose weight through lifestyle changes and medication alone. However, more evidence is necessary to show non-inferiority of e-health compared to in-person monitoring with regard to important parameters for the success of surgical treatment of obesity such as anthropometric changes. Methods and analyses This review study will include cohort studies involving individuals with obesity and e-health or in-person patient monitoring before and after MBS. This study protocol was registered in the PROSPERO (CRD42023491051). We will conduct searches in the following databases: PubMed, EMBASE (Elsevier), Cochrane (CENTRAL), Web of Science, SCOPUS and CINAHL (EBSCO) and LILACS-VHL. We will also search databases in the gray literature. The primary outcomes will be changes in body mass index (BMI), body weight (kg) and body fat percentage (BF%) and patient adherence and satisfaction. The risk of bias of individual eligible studies will be assessed using the Newcastle-Ottawa Scale and the overall quality will be assessed using the GRADE tool. Our analyses will involve comparisons of mean differences or standardized mean differences across the groups using random-effects models and 95% confidence intervals. Statistical analyses will be performed with RStudio for Windows (v1.3.959) using R package meta (v3.6.1). Discussion and conclusion Our study can offer evidence that shows the benefits of e-health patient monitoring of individuals undergoing MBS and supports scaling up this care modality to reduce waiting times and health care costs.